Iron(III) tosylate hexahydrate (Fe(OTs)3⋅ 6H2O), a green Water-Tolerant Lewis acid catalyst for the synthesis of Bis(indolyl)methanes in benign conditions - Akanksha Mishra; Mrinal Talukdar; Alpa Y. Dave; Eeshwaraiah Begari (Results in Chemistry)
Fe(OTs)3·6H2O, a water-tolerant Lewis acid catalyst for electrophilic substitution of aldehydes with indole, produces bis(indolyl)methane through an environment-friendly and green procedure. With its low sensitivity to oxygen, great tolerance to diverse functional groups, green reaction media, and outstanding yields, this procedure is an effective method for synthesizing bis(indolyl)methane under relatively benign circumstances, making it suited for both laboratory and industrial use.